Update on Hepatitis C 2017
DOI: 10.5772/intechopen.70437
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Treatment in Elderly Patients

Abstract: The patients with chronic hepatitis C (CHC) are geting older and the demands for treatment to those patients are increasing due to the high risk of development of hepatocellular carcinoma. Elderly patients were previously deined as 60 years and over, however deinition of the elderly patients shifted to be older year to year. Interferon (IFN) and ribavirin combination therapy was signiicantly improved eicacy of treatment, however ribavirin induces anemia, resulted in lower eicacy due to reduction of ribavirin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…BCAAs supplementation in obese/diabetic mice appears to suppress hepatic de novo lipogenesis and promote adipocyte lipolysis, causing abnormal lipolysis and hyperlipidemia, and liver injury (Zhang et al, 2016;Iwao et al, 2020;Zhao et al, 2020). In contrast, research on nonalcoholic steatohepatitis mice showed that BCAAs supplementation alleviated hepatic steatosis and liver injury by suppressing the expression of lipogenesis-related genes and proteins (Honda et al, 2017). Thus, it is necessary to further clarify the effect of BCAAs on the liver and the possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…BCAAs supplementation in obese/diabetic mice appears to suppress hepatic de novo lipogenesis and promote adipocyte lipolysis, causing abnormal lipolysis and hyperlipidemia, and liver injury (Zhang et al, 2016;Iwao et al, 2020;Zhao et al, 2020). In contrast, research on nonalcoholic steatohepatitis mice showed that BCAAs supplementation alleviated hepatic steatosis and liver injury by suppressing the expression of lipogenesis-related genes and proteins (Honda et al, 2017). Thus, it is necessary to further clarify the effect of BCAAs on the liver and the possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…L-Isoleucine is a Branchedchain amino acids (BCAA). Previous studies have reported that BCAAs can promote fatty acid b-oxidation and ketone body production (19). b-oxidation is thought to be the main mechanism of hepatic lipid reduction and is involved in the upregulation of peroxisome and mitochondrial genes (20).…”
Section: Discussionmentioning
confidence: 99%